Establishment of fluoroscopy views and standardized procedure of percutaneous magic screw insertion for acetabulum fractures - Li, Jiantao (BMC Musculoskelet Disord, 2018)
BACKGROUND: To place the magic screw more simply, we established a set of reproducible fluoroscopic views and a standardized procedure of magic screw insertion. MATERIALS AND METHODS: This study on the magic screw tunnel uses a three-dimensional reconstruction model and a skeleton projection. The 3D model of the pelvis was made to be transparent and it was rotated to the place where the ischial spine was just sheltered by the posterior wall of the acetabulum. The angles of this view projection were recorded in the transverse plane and coronal plane. Six cadaveric pelvises (three males, three female) were used to validate the proper projection angle of the C-arm fluoroscopy. The skeleton specimens were all positioned latericumbent on a radiolucent table. RESULT: In all pelvis 3D models, all magic cylinders with a 7.3 mm diameter were successfully inserted along the bone structure tunnel in 30 3D pelvic models. The average angle of the transverse view rotated by the C-arm fluoroscopy was 162° in males and 157° in females, the angle of the coronal plane was 22° in males and 24° in females. The average distance between the front wheel of the C-arm machine and the middle axial line of the radiolucent bed was 43 cm in males and 43 cm in females. In skeleton pelvis research, all the screws were safely inserted using this method. CONCLUSION: The magic screw technique could be a good choice for the treatment of acetabular fractures, especially quadrilateral plate fractures. If the proper fluoroscopy view technique is used properly, the magic screw can be inserted rapidly and safely.